Autoimmune polyglandular syndrome type 3 variant in rheumatoid arthritis - Horino Taro; Ogasawara Masami; Ichii Osamu; Terada Yoshio (Sciendo, 2020)
Introduction. Although type 1 diabetes mellitus is largely associated with autoimmune thyroid disease and this entity has been recently referred to as autoimmune polyglandular syndrome type 3 variant, the autoimmune polyglandular syndrome type 3 variant in patients with rheumatoid arthritis has not been reported so far. We herein describe the first case of rheumatoid arthritis that was associated with autoimmune polyglandular syndrome type 3 variant.